In vitro antifungal activity of biosynthesized selenium nanoparticles using plant extracts and six comparators against clinical Fusarium strains - Mohsen Nosratabadi; Mohammad Ali Ebrahimzadeh; Seyedeh Roya Alizadeh; Iman Haghani; Leila Faeli; Robab Ebrahimi Barogh; Abdullah Al-Hatmi; Mahdi Abastabar (Mazandaran University of Medical Sciences, 2024)
Background and Purpose: Fusarium species are commonly resistant to many antifungal drugs. The limited therapeutic options available have led to a surge of research efforts aimed at discovering novel antifungal compounds in recent decades. This study aimed to assess the in vitro antifungal activity of plant-based biosynthesized selenium nanoparticles (Se NPs) and six comparators against a set of clinical Fusarium strains.Materials and Methods: In vitro antifungal activity of Se NPs synthesized using plant extracts of Allium paradoxum, Crocus caspius, Pistacia vera L. hull, Vicia faba L. hull and Heracleum persicum, as well as six common antifungal drugs; voriconazole, itraconazole, amphotericin B, posaconazole, natamycin, and caspofungin were evaluated against 94 clinical Fusarium strains using broth microdilution according to Clinical and Laboratory Standards Institute (CLSI) guideline. Results: The obtained results were intriguing because all five types of biosynthesized Se NPs demonstrated significantly higher antifungal activity compared to antifungal drugs. Se NPs synthesized by V. faba L. hull extract (0.03 μg/ml) had the lowest geometric mean (GM) MIC value followed by Se NPs synthesized by P. vera L. hull extract (0.25 μg/ml), Se NPs synthesized by A. paradoxum extract (0.39 μg/ml), Se NPs synthesized by C. caspius extract (0.55 μg/ml), and Se NPs synthesized by H. persicum extract (0.9 μg/ml).Conclusion: Plant-based Se NPs demonstrated supreme antifungal activity and could be considered promising antifungal agents for Fusarium infections. However, tests like toxicity and in vivo tests are needed before the product can be used in clinical settings.